The Development of Pictorial Dictionary for Learning Dusun Language - Augustin, Nyzveldo; aziz, ruhaya (Applied Information Technology And Computer Science, 2021)
The developed project is a web-based dictionary for learning Dusun Language. The purpose of this project is to develop a pictorial dictionary for learning Dusun Language. The dictionary specifically able to translate Malay to Dusun Language and vice versa. The system also help user to understand how to use the word by using the example of sentences using the word searched or selected by the user. This system also provides pronunciation or speech out for the word selected by user, make user easier to pronouns the words. The word selected by the user will be also included with its definition, Synonym to help the user understand more of the word. Comparison with another similar system such as English -KadazanTranslator's Companion had been done as the result been taken to build this system that fulfills what the current system does not have. This system was developed based on the Iterative Model. The outcome of this system is expected can help any user or consumer that wanted to learn Dusun or need to translate Malay language to Dusun. Thus, this system is to help the consumer or user to make decision based on the word they want to use in conversation. Therefore, this system has a great potential in helping user to learn Dusun language.